2021
DOI: 10.3145/epi.2021.mar.13
|View full text |Cite
|
Sign up to set email alerts
|

Training in digital competencies for health professionals: systematic mapping (2015-2019)

Abstract: Digital competencies are one of the main transversal competencies of the XXI century. By means of systematic mapping, international published papers and research on digital skills training were critically evaluated, generating a process that helps us to recognize information about health professionals and the type of educational technology used in training. With this in mind, we employed the systematic mapping method using the WoS and Scopus databases between 2015 and 2019 in English and Spanish, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…The results of RQ3 provided the geographical location of those who publish on mediation and online learning, showing interest to be mainly in the United States and other countries such as Taiwan and China. Similar results were found by [38], where the United States dominates as the country from which it is most published, therefore, research in these areas of interest to other latitudes must be strengthened. It is important to reflect that in the research, interest in the topic was also found from several regions, since even with a few contributions in this area, they are researching on mediation and online learning.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of RQ3 provided the geographical location of those who publish on mediation and online learning, showing interest to be mainly in the United States and other countries such as Taiwan and China. Similar results were found by [38], where the United States dominates as the country from which it is most published, therefore, research in these areas of interest to other latitudes must be strengthened. It is important to reflect that in the research, interest in the topic was also found from several regions, since even with a few contributions in this area, they are researching on mediation and online learning.…”
Section: Discussionsupporting
confidence: 63%
“…Another of the publications analyzed within the literature reviews was the country to which the authors belong, which shows where the studies mostly come from. This is how we found the work called Training in Digital Competencies for Health Professionals: Systematic Mapping (2015-2019) [38]. As mentioned in the previous paragraph, the literature reviews that emerge from the search chain do not address the same questions and aspects of interest the topics as in this study; however, it is important to highlight the literature review's identification and prioritization of critical issues for the promotion of e-learning in Pakistan, where the analysis focuses on the critical e-learning themes [39] and Trends in Educational Research about e-Learning: A Systematic Literature Review (2009-2018), which addresses e-learning as a technology-mediated learning approach [40].…”
Section: Introductionmentioning
confidence: 82%
“…What's more, the document type of the studied publications was restricted to "article". As shown in Table 2, a set of inclusion and exclusion norms was defined to remove the unrelated data [21]. Eventually, after the double check made by the authors, a total of 3058 final samples with their bibliometric information obtained from the WoS were derived in the form of TXT.…”
Section: A Data Collectionmentioning
confidence: 99%
“…Cabe destacar la preocupación de la Comisión Europea por mejorar la alfabetización digital de los ciudadanos, poniendo en marcha el Plan de Acción de Educación Digital para el período 2021-2027 cuyo objetivo es aumentar la proporción de ciudadanos europeos que posean competencias digitales hasta el 70% en 2025 (Comisión Europea, 2021), poniendo de relieve la figura del docente como responsable de la alfabetización digital de sus estudiantes (García-Ruiz & Pérez Escoda, 2021;Redecker & Punie, 2017). La CDD en la última década, y de manera destacada a partir de 2020, ha sido reconocida como una de las competencias claves para el ejercicio de la profesión docente de cualquier nivel educativo (Dervenis et al, 2022;Fernández-Luque, 2021).…”
Section: Introductionunclassified